PENGARUH PERMAINAN KOTAK MISTERI TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 3 KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Devi Purnama Sari; Zulkifli N; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of field observations on the ability to recognize the shape of the geometry of students has not developed optimally. So it is necessary to apply the game mystery box. The purpose of this study was to determine the effect of mystery box games on the ability to recognize the shape of geometry in children 4-5 years old at TK Negeri Pembina 3 Marpoyan Damai District Pekanbaru City. This study used an experimental method with the design of the pretest-posttest control research group design. The population in this study were children aged 4-5 years totaling 36 children and the sample used were non-probability sampling with random sampling techniques using lottery. In this study a sample of 36 children divided into two classes, the division was done by insidental sampling so that the experimental class was 18 children and the control class was 18 children. The data collection techniques used are observation. Data analysis techniques use the t-test. The results of this research hypothesis test obtained t = 10,807 with Sig. (2-Tailed) = 0,000 < 0,05, which means that there is an of the ability to recognize a very significant geometric shapes after using the mystery box game during the learning process. The impact of mystery box games on ability to recognize the shape of geometry in children 4-5 years old at TK Negeri Pembina 3 Marpoyan Damai District Pekanbaru City amounting to 58,97% included in the medium category.Key Words: Geometry Shape, Box Mystery.